Analisis Tingkat Resiko Dan Imbal Hasil Saham Terhadap Pembentukan Portofolio Optimal - Soelehan, Aan; Yudha, Andi; Chandra, Bella Dian (LPPM Institut Bisnis dan Informatika Kesatuan, 2014)
This research is conducted to determine the optimum portfolio and analyze the risks and returns that will be yieldedfrom six shares in selected stocks based on the most stable movements in the last three years. The data used in this study are secondary data obtained from Indonesia Stock Exchange (IDX). The analysis techniques are using formulas in a portfolio started with calculating the risk and returns to determine stocks classified in the optimum portfolio through ERB calculation. In the year 2010, of the six shares researched, there are 4 shares included in optimum portfolios, which are Bank Danamon Indonesia Tbk, with 39.36% portion of investment, United Tractors Tbk with 49.3%, Aneka Tambang (Persero) Tbk with 2.33% and Bank Mandiri (Persero) Tbk with 9.01 %. In the year 2011, there are 3 shares included in the optimum portfolios, which are Perusahaan Gas Negara (Persero) Tbk with 11.95% portions United Tractors Tbk. with 73.80% and Medco Energi Intemasional Tbk with 14.25%. in the year 2012 of the six shares studied only one share has the ERB value > Ci, thus cannot form optimum porfolio due to share member used do not meet the criteria. Keywords: Rate ofReturn, Risk, Optimum Portfolio